CAPITALISM: COMPETITION, CONFLICT, CRISES, ANWAR SHAIKH - Martínez Hernández, Francisco A.; Isidro Luna, Víctor M. (Investigación Económica, 2019)
In 1,024 pages, seventeen chapters, and divided in three books, plus seventeen appendixes, Anwar Shaikh, one of the leading scholars and a distinguished Professor of Economics at the New School for Social Research, presents a path breaking and monumental book which main objective is the unified study of the logic, history, dynamics, and crises of the capitalist system. Throughout this book, the author confronts his own perspective and method of the classical political economy with major schools of economic thought such as neoclassical, monetarist, and different branches of the post-Keynesian school...